Intercept of Financial, Economic and Educational Transformations: Bibliometric Analysis - Vladislav Novikov (Financial Markets, Institutions and Risks)
Financial, economic and educational transformations might be clarified from very different perspectives. Economic transformations are used to identify as changes in value added contribution of some branch in its formation at national level, or its productivity. Nowadays economic transformation are by far wider and more complicated process because of intensification of globalization, integration and digitalization of economic relationship over the last few decades. Financial transformations are also caused by intensification of globalization, integration and digitalization of economic relationship and might be identified through characteristics of the scale of financialization in curtain country and all over the world. Expansion of financialization and digitalization trends led to relevant changes in financial products characteristics, ways of its distribution and promotion, and general relevance of financial sector in macroeconomic stability and sustainable economic growth. Digitalization and COVID-19 pandemic also led to considerable challenges and transformation of education system. Education process are needed to be based on modern pedagogical, technological and scientific approaches. It became crucial to not only disseminate traditional knowledge and ensure of obtaining hard skills, but also make students enriched with soft skills. Traditional learning process accompanied with physical visiting of classes and writing a thesis are no more relevant, so e-learning and distance learning technologies are an integral part of educational process nowadays. It is became obvious that economic, financial and education transformation are connected somehow and converged but there is lack of researches aimed at specification of their intercept and cohesion. Therefore, this research aimed at clarification of intercept between financial, economic and education transformations has both theoretical value and might have practical implication for policymakers. It is realized using VOSviewer tool based on publications in Scopus on financial, educational and economic transformations 1990–2020. Therefore, bibliometric analysis allow concluding that there are both common and specific clusters of scientific researches on economic, financial and educational transformations. Namely, all three types of transformations are somehow dependent on health care system, environmental determinants, social aspects, etc. It can be pointed out that these transformations have common preconditions, consequences and ways of implementation. This may leads to conclusion that there are some convergence between educational, financial and economic transformations.